PENGARUH KONSUMSI BUAH PISANG AMBON TERHADAP MEMORI JANGKA PENDEK WANITA USIA DEWASA TENGAH DI WILAYAH KERJA PUSKESMAS III DENPASAR UTARA - Ratna Sawitri (Coping: Community of Publishing in Nursing, 2014)
During growth and development to adulthood, there are cognitive changes such as memory loss. This memory loss is one of the characteristics of dementia. Memory decline in middle adulthood (35-59 years) occurs when the short-term memory is less frequently used than the long-term memory. Nutrition can improve short-term memory abilities, one of them by giving food and beverages with sugar content that enough for the body. Banana contain simple sugars are quickly digested into glucose and blood to the formation of the body's energy. This study aimed to know the effect of consumption of Ambon’s banana on short-term memory in middle adult women. This study was a quasi-experiment study with pretest-posttest with control group design. The sample consisted of 30 people who were selected by purposive sampling, were divided into two groups: treatment and control. Data was collected through interviews with assessment tests measuring devices through a range of numbers. The results of the study are the mean value before and after given consumption of ambon’s bananas in the treatment group amounted to 8.47 and 9.80. While the mean value before and after the observations in the control group are 8.07 and 8.27. Based on the Mann-Whitney test this difference was statistically significant with a significance level of p = 0.000 that means consumption of ambon’s banana influences the short-term memory in middle adult women. Based on this study we advise to middle adult women to eating ambon’s banana for preventing dementia.